PERBEDAAN GENDER DALAM KETERAMPILAN BERPIKIR ANALITIS DAN LITERASI KIMIA - eka - adhiya; A. Rachman Ibrahim (Jurnal Penelitian Pendidikan Kimia: Kajian Hasil Penelitian Pendidikan Kimia, 2019)
This study aims to investigate the effect of the differences between genders on analytical thingking skills and Chemical literacy. A sampel of 212 (88 males and 124 females) senior high school in Yogyakarta, Indonesia completed the survey. The instruments used are 20 open-ended multiple choice integrated assessment instruments. This study used Independent T-Test to compared the males and females mean. The result showed that no signicant (sig>0.05) gender differences were found in analytical thinking skills and Chemical literacy. Male and female have analytical thinking skills and Chemical literacy equally.